PENERAPAN PENDEKATAN STEAM UNTUK MELATIH KETERAMPILAN BERPIKIR KRITIS SISWA DI SMP KELAS VII KOTA AMBON - Carolina Sri Athena Barus; Sally E. Untajana; Fryan Sopacua; Venty Sopacua; Jhony Taihuttu; Herman Samuel Wattimena; Cicylia Triratna Kereh; Juliana Nirahua; Asry N. Latupeirissa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to enhance students’ critical thinking skills through the implementation of the Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach at a public junior high school in Ambon City. A quasi-experimental design was employed, with the population consisting of all seventh-grade students in the even semester across two classes. The sample was selected using simple random sampling, comprising 23 students from class VII-1. Data were collected using a 10-item essay test measuring five indicators of critical thinking skills: elementary clarification, the basis for the decision/basic support, advanced clarification, inference, and strategies and tactics. Descriptive quantitative and qualitative analysis techniques were applied to evaluate the data. Results showed a significant improvement in all critical thinking indicators after the STEAM intervention, with the highest achievement in elementary clarification (68.75). The findings indicate that the STEAM approach effectively fosters systematic and analytical thinking by integrating conceptual knowledge, creativity, and scientific reasoning. Thus, STEAM-based learning is a promising strategy to strengthen higher-order thinking skills in junior high school science education.